Meretas Konsep Baru Pidana Denda Terhadap Tindak Pidana Korupsi: Analisis Komparatif dengan Foreign Corrupt Practices Act Amerika Serikat, Bribery Act Inggris, dan Wetboek van Strafrecht Belanda - Valerian, Dion (Integritas : Jurnal Antikorupsi, 2019)
Indonesian Anti-Corruption Act stipulates its criminal fines provision by determining a fixed amount of fines in its criminal offences formulation. This article analyses and compares the concept of criminal fines in the Indonesian Anti-Corruption Act, the United States Foreign Corrupt Practices Act, United Kingdom Bribery Act, and the Dutch Criminal Code. The study found that each of the aforementioned US, UK, and Dutch anti-bribery laws have its distinctive concept to overcome the problem of criminal fines provision’s astringency that could be used in the Indonesian Anti-Corruption Act reform.